Empirical effects of sanctions and support measures on stock prices and exchange rates in the Russia-Ukraine war - Jens Klose (Philipps-University Marburg, School of Business and Economics, 2023)
What are the effects of sanctions and economic support on stock prices and exchange rates in the Russia-Ukraine war? We address this question using a panel-VAR model that incorporates data from 23 countries, besides Russia and Ukraine, spanning the period from 02/01/2022 to 02/24/2023. Our analysis relies on a detailed database to capture the nuances of sanctions and economic support. The results are presented from three distinct perspectives: firstly, in relation to the global economies; secondly, with regard to Russia; and thirdly, concerning Ukraine. The findings reveal that the overall impact of economic support provided to Ukraine is generally limited. In contrast, sanctions imposed by countries have minimal effects on the sanctioning country itself, but they can have significant consequences for the targeted nation. This is particularly evident when financial sanctions are implemented. However, it is important to note that such sanctions also exert effects on the opposing party in the war, Ukraine. Furthermore, if the sanctions originate from G7 or developed countries, the effects on Russia tend to be more pronounced.
Keywords: F31; F51; G15; C33; 330; Sanctions; Support Measures; Stock Prices; Exchange Rates; Panel-VAR